Interrupted tension-tension fatigue behavior of angle-ply GFRP composite laminates. (August 2018) - Movahedi-Rad, A. Vahid; Keller, Thomas; Vassilopoulos, Anastasios P.
Highlights: Interrupted fatigue behavior of (±45)2s GFRP laminate was investigated. Different stress levels led to different damage distributions. More uniformed damage distributions was observed by applying interrupted fatigue. Total dissipated energy was greater in interrupted fatigue experiments. Fatigue design allowables may be conservative. Abstract: The effect of load interruptions on the tension-tension fatigue behavior of angle-ply (±45)2S glass/epoxy composite laminates was investigated. The cyclic loading was interrupted for two hours at regular cycle intervals, corresponding to 20% of the fatigue life under continuous loading at the same maximum cyclic stress level. Fatigue stiffness was partially restored after each loading interruption due to the recovery of the viscoelastic polymeric matrix. This repeated material stiffening at the beginning of each loading block delayed crack growth. Crack blunting further delayed damage growth and caused a more uniform damage distribution throughout the specimen volume. By applying interrupted fatigue loading, the rates of stiffness degradation and energy dissipation per cycle decreased due to the delayed damage growth. In addition, more uniform damage growth throughout the specimen volume increased the specimen's capacity to accumulate damage, which led to a lower stiffness at failure, greater energy dissipation per cycle at failure and higher total dissipated energy of specimens subjected to interrupted loading. The specimens loaded under interrupted fatigue therefore exhibited longer fatigue lives than those continuously loaded. This enhancement of fatigue life increased at higher stress levels but almost disappeared at low levels. It was thus concluded that fatigue design allowables, if determined on the basis of continuous fatigue, are conservative in the case of interrupted fatigue.